Changes of Prothrombin Fragment 1+2 (F 1+2) as a Function of Increasing Intensity of Oral Anticoagulation - Tripodi, Armando; Cattaneo, Marco; Molteni, Alfredo; Cesana, Bruno M.; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1998)
Plasma F 1+2 levels, the activation peptide originating from the factor Xa-mediated activation of prothrombin, increase in many clinical conditions associated with hypercoagulability and decrease in patients on oral anticoagulant treatment (OAT). However, the usefulness of F 1+2 measurement to monitor OAT has not yet been investigated in clinical studies. Before those studies are attempted, the plausibility of its implementation in the laboratory control of OAT should be evaluated. In this respect, a thorough investigation of the pattern of changes of F 1+2 as a function of increased intensity of anticoagulation expressed as International Normalized Ratio is essential. One hundred and thirty-two patients on long-term warfarin treatment were recruited to cover 8 ranges of anticoagulation from <1.5 to 9.0 INR. F 1+2 was measured in batch on frozen plasma and INR was determined on fresh plasma. The relationship of F 1+2 vs. INR showed a hyperbolic pattern with F 1+2 levels decreasing progressively and significantly as a function of increasing INR up to 3.0. A further decrease in F 1+2 levels observed at INR up to 4.0 was not statistically significant. At INR greater than 4.0, F 1+2 reached a plateau, with mean levels not significantly different for patients at increasing INR up to 9.0. Since the risk of bleeding increases at INR greater than 4.5, our results suggest that F 1+2 is of little value to assess the hemorrhagic risk in patients on OAT.